CLINIC AND THERAPEUTIC ASPECTS IN DUCTUS-DEPENDENT CONGENITAL HEART DEFECTS (PART II) - Alina-Costina Luca; Andreea-Simona Holoc; Mirabela Subotnicu; Constantin Iordache (Amaltea Medical Publishing House, 2015)
The cardiac congenital malformations with duct dependent pulmonary circulation are cardiopathies with severe neonatal manifestations and quickly progressive hemodynamic degradation. The obvious semeiology at the birth requires an appropriate diagnostic and an early therapeutic management through the maintenance of the arterial channel permeability.